PERSEPSI PELANGGAN TERHADAP KUALITAS DAN HARGA PRODUK RESTORAN STUDI KASUS PADA RESTORAN JANGGAR ULAM DI KAWASAN PARIWISATA UBUD, BALI. - I Nyoman Rinala (Jurnal Ilmiah Hospitality Management, 2015)
The restauranteur need to improve their product or service quality and always develop their innovation to play tight competition in restaurant business. Restaurant managers are suppose to have a better understanding about service excellence model to attract, to maximize, and to achieve customer loyalty. Each restaurant manager has a specific consideration in prioritizing determinant factors to achieve customer satisfaction and customer loyalty. This research was undertaken at Janggar Ulam Restaurant, Ubud, Gianyar regency between May to August 2014. The objective of this reseach is to identify the determinant atributtes of restaurant’s service which influenced customer’s perception on quality and price. Customers in this research consist of four groups, such as: foreign tourists, domestic tourists, business travelers, and local or family segment. This research is qualitative approach research based on group interview focus and technique. Finally, the conclusion of this research shows customer’s perception on quality  and price at Jangar Ulam restaurant were determined by: (1) food quality; (2) atmosphere and ambience; (3) service quality; (4) price; (5) location of restaurant; (6) parking; (7) social media and friend’s recommendation; and (8) facility offered (free internet/wifi access, children play area).